Identification of Corynebacterium bovis by MALDI-mass spectrometry - Langoni, Hello [UNESP]; Camargo da Silva, Carolina Polo [UNESP]; Troncarelli, Marcella Zampoli; Tata, Alessandra; Anacleto Belaz, Katia Roberta; Eberlin, Marcos Nogueira; Joaquim, Samea Fernandes [UNESP]; Guimaraes, Felipe Freitas [UNESP]; Pardo, Renata Bonini; Gomes, Eduardo Nardini [UNESP] (Elsevier B.V., 2017)
Corynebacterium bovis is a mastitis-causing microorganism responsible for economic losses related to decrease in milk production. The aim of the study was identify Corynebacterium, spp. strains recovered from milk samples of subclinical mastitis by using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Samples were collected during a 10-mo mastitis-monitoring program in a high-production dairy farm. In this study, 80 strains were analyzed; from these 54 (67.5%) were identified at species level as Corynebacterium bovis, 24 (31.2%) isolates were identified at the genus level as Corynebacterium spp., and only 1 (1.35%) isolated had unreliable identification. Results demonstrated that MALDI-MS could be an important technique for the identification of Corynebacterium spp. in milk.
Keywords: mastitis; Corynebacterium bovis; proteomic characterization